2007
DOI: 10.1182/blood-2006-10-054080
|View full text |Cite
|
Sign up to set email alerts
|

Premature cardiovascular disease after allogeneic hematopoietic stem-cell transplantation

Abstract: We assessed incidence and risk factors of cardiovascular events in 265 patients undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) between 1980 and 2000 and who survived at least 2 years. Results were compared with a cohort of 145 patients treated during the same period with autologous HSCT. The median age of patients with allogeneic HSCT at last follow-up was 39 years, and median follow-up was 9 years. Eighteen (6.8%) patients after allogeneic and 3 (2.1%) patients after autologous HSCT expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
191
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(205 citation statements)
references
References 39 publications
12
191
0
2
Order By: Relevance
“…8,9 In our study, diabetes, hypothyroidism and hyperlipidemia were observed in 4 (11%), 9 (26%) and 10 (30%) patients, respectively. One patient had myocardial infarction.…”
supporting
confidence: 49%
“…8,9 In our study, diabetes, hypothyroidism and hyperlipidemia were observed in 4 (11%), 9 (26%) and 10 (30%) patients, respectively. One patient had myocardial infarction.…”
supporting
confidence: 49%
“…A recent retrospective single-center cohort study showed that long-term survivors post allo-HSCT are at risk for cardiovascular disease, as compared with patients treated with autologous transplantation. 29 Baker et al 30 have found that HSCT survivors have a higher risk of diabetes and hypertension, which potentially lead to higher cardiovascular events. In our univariate and multivariate analyses age group, conditioning therapy (TBI-based vs non-TBIbased), transplant type (related vs unrelated), primary diagnosis or chronic GVHD did not seem as risk factors for CAD (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes was often associated with other cardiovascular risk factors, such as arterial hypertension, dyslipidemia and unhealthy heart lifestyle. [67][68][69] In summary, hyperglycemia after allo-HSCT is common and is associated with an increase in morbidity and NRM.…”
Section: Ptdm and Clinical Outcomesmentioning
confidence: 99%